The effect of ATP sulphurylase on the prooxidant properties of selenate in yeast Schizosaccharomyces pombe - Fujs, Štefan (Array, 2009)
Summary: Selenium is an essential microelement in human and animal nutrition, whose intake can be in inorganic (e.g. selenite, selenate) or organic form (e.g. selenomethionine). The prooxidant effect of inorganic selenium sources in the animal nutrition has been found as a great disadvantage. Therefore, in this study the effect of the ATP sulphurylase on the prooxidant properties and toxicity of selenate in the fission yeast model organism Schizosaccharomyces pombe has been studied. Two strains of yeast Schizosaccharomyces pombe were used, selenate resistant (SeR) ZIM 1889 and selenate sensitive (SeS) ZIM 1878 strains, with inactive and active ATP sulphurylase, respectively. During the yeasts’ exposure to selenate growth, intracellular oxidation, cell viability and antioxidative defence systems were determined. Also, activities of antioxidative enzymes (catalase, superoxide dismutases, glutathione peroxidase, glutathione reductase and glucose-6-phosphate dehydrogenase) and intracellular content of reduced glutathione were measured. The results show altered enzymatic activities and decreased intracellular content of reduced form of glutathione in the selenate sensitive strain as a consequence of active ATP sulphurylase, which enables selenate reduction leading to oxidative stress. During the selenate reduction, reactive oxygen species (ROS) are generated and therefore antioxidative defence systems are induced. In contrast, in the selenate resistant strain with inactive ATP sulphurylase, where selenate reduction does not occur, no induction of antioxidative defence systems was found. Consequently, the active ATP sulphurylase is the key enzyme for the prooxidant properties of selenate and it seems to be the main reason for selenate toxicity and ROS formation during the selenate reduction